Autistic people's family and emotional intelligence - Chaidi , Irene; Drigas, Athanasios; Karagiannidis, Charalampos (Technium Social Sciences Journal, 2021)
In recent years there has been a growing interest in people on the autism spectrum but also the impact it has on their families, both in terms of the cohesion and relationship that develops between its members and its emotional intelligence. The aim of this work is through the literature review a) to depict the emotional intelligence of families with a person on the autism spectrum b) to present the research findings c) to present the factors that affect the emotional intelligence of families